The influences of pulsed-laser-ablation and electro-discharge-grinding processes on the cutting performances of polycrystalline diamond micro-drills. Issue 1 (2016) - Butler-Smith, Paul; Warhanek, Maximilian; Axinte, Dragos; Fay, Michael; Bucourt, Jean-Francois; Ragueneau, Raphael; Wegener, Konrad
Abstract: Geometrically complex micro-tools are manufactured via processes which can affect their cutting performances. This paper studies the effects pulsed-laser-ablation and electro-discharge-grinding on polycrystalline diamond matrices and their binder phases at nanometric scales, revealing distinct differences in the resulting substructures. The dissimilarities in micro-scale material removal phenomena of these manufacturing processes combined with their effects on the generated surface topographies and cutting-edge geometries can significantly influence the wear and cutting performance of micro-drills. A study on the micro-drilling of a ceramic matrix composite workpiece material confirms that pulsed-laser-ablation of composite diamond structures offers a step-change in the fabrication of micro-tools.